Assessment of the success rate of specialised female surgical clinic in tertiary care hospital - Gupta, Anand; Sharma, Anshuman (International Surgery Journal, 2019)
Background: Specialized female surgical clinics are the basic requirement in surgical department which should be addressed routinely. The management of surgical problems in female patients requires multidisciplinary approach mainly general surgery, obstetrics and gynaecology, general medicine, paediatrics, dermatology and psychiatry. If proper care is provided then this will uplift the follow up of same patients in such clinics. The objective of the study was to assess the success rate of female surgical clinics and to determine the follow up visits done by female patients once visited the female surgical clinics. Methods: Prospective educational interventional study was conducted. A total of 952 patients visiting the clinic were studied. Statistical analysis was done. Results: Out of 952 cases 944 (99.2%) cases were willing to continue visit to the clinic, while 809 (84.9%) cases revisited for follow up treatment in female surgical clinics within one year duration. Conclusions: It can be concluded that there is a requirement and need of a fully functional specialized female surgical clinic in our hospital. As the success rate for follow up visit by patients in this clinic was high.